Low Wage Jobs and Pathways to Better Outcomes - Sue Richardson; Lauren Miller-Lewis (New Zealand Government, The Treasury, 2002)
Many people find their first employment in a low wage job. Others accept low wage jobs after a period out of the workforce or unemployed. An issue of vital social interest is the speed with which low wage workers move on to better jobs. This review of the international literature finds that the extent of mobility depends on the definition of low wage, and that the least upwardly mobile are older, less educated workers, including middle aged women, sole mothers and men who have been retrenched. Young, educated, urban workers quickly move to better paid jobs. Everywhere, women are more likely to be low paid than men, and have lower mobility. Higher education reduces the risk of low pay, but not to zero. The paper goes on to examine the extent and sources of wage mobility, and looks carefully at the question of whether a low wage job can be assumed to be preferable to no job (and finds that it cannot). It finds that countries with high levels of wage inequality have lower levels of wage mobility. It concludes with a discussion of possible policy steps that could reduce the risk of people being stuck in low wage jobs for long periods. These should be targeted at both the demand side (the structure of jobs) and the supply side (the capacity of workers).
Keywords: J30; J60; 330; Low wages; mobility; work and welfare; low wage workers.